Non-infected preterm parturition is related to increased concentrations of IL-6, IL-8 and MCP-1 in human cervix - Brauner Annelie; Chromek Milan; Byström Birgitta; Klimaviciute Aurelija; Törnblom Susanne; Ekman-Ordeberg Gunvor (BMC, 2005)
Abstract Background Human cervical ripening is an inflammatory process. In labour at term the mRNA-levels and protein concentrations for interleukin-6 (IL-6) and IL-8 in cervix significantly increase. The aim of this study was to investigate if there are differences in the inflammatory process of preterm and term cervical ripening. Methods Cervical biopsies from 50 singleton pregnant women without clinical signs of infection were allocated to four groups: preterm labour, term labour, preterm not in labour and term not in labour. The protein levels of IL-8, IL-6, monocyte chemotactic protein-1 (MCP-1), regulated upon activation normal t cells expressed and secreted (RANTES) and tumour necrosis factor-alpha (TNF-alpha) were quantified in tissue homogenates by ELISA or Immulite. The mRNA expression of IL-8, MCP-1 and RANTES was studied using RT-PCR. White blood cell count (WBC) and C-reactive protein (CRP) in the blood were determined. For determination of statistically significant differences between study groups Mann-Whitney U test or Kruskal-Wallis test were applied. Results Protein concentrations of IL-8, IL-6, and MCP-1 were significantly increased during labour compared to non-labouring groups, whereas no changes were observed for RANTES and TNF-alpha. The mRNA levels of representative cytokines such as IL-8 and MCP-1 increased significantly during labour whereas RANTES mRNA expression remained unchanged. WBC and CRP were significantly higher in the labouring groups as compared to groups not in labour. For neither of the analysed cytokines, WBC or CRP levels were there any changes between preterm and term respective groups. Conclusion Our findings indicate that non-infected preterm cervical ripening is an inflammatory process, just as cervical ripening at term, with cytokines as important mediators.